2007
DOI: 10.1016/j.pbb.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol intake modulates photic and non-photic circadian phase responses in the Syrian hamster

Abstract: Chronic alcohol intake disrupts sleep and other circadian biological rhythms in both human alcoholics and in experimental animals. Recent studies from our laboratory indicate that these effects may be due, in part, to ethanol-induced alterations in fundamental properties of the circadian pacemaker. The present study explored the effects of chronic voluntary ethanol intake (25% v/v) on circadian phase responses to both photic and non-photic stimuli in Syrian hamsters. Hamsters were used in these experiments bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 43 publications
8
36
0
Order By: Relevance
“…This result is largely consistent with a previous study in chronically drinking hamsters where EtOH inhibited photic advances but not delays (81). The basis of this differential effect of EtOH on phase resetting is not clear but could reflect a distinct inhibitory action directed at a component of the intracellular photic clock-resetting pathway devoted to phase-advance shifting.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is largely consistent with a previous study in chronically drinking hamsters where EtOH inhibited photic advances but not delays (81). The basis of this differential effect of EtOH on phase resetting is not clear but could reflect a distinct inhibitory action directed at a component of the intracellular photic clock-resetting pathway devoted to phase-advance shifting.…”
Section: Discussionsupporting
confidence: 91%
“…In hamsters, for example, chronic drinking is reported to have minor effects on circadian rhythm stability and period characteristics and does not impede the rate of reentrainment to a shifted LD cycle (51). On the other hand, chronic EtOH has been shown reduce light pulse-induced phase advances (but not phase delays) and inhibit phase advance shifts to triazolam (81). In rats, chronic EtOH alters the free-running period under DD but apparently has no effect on photic phase resetting (77,78).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the number of neurons containing vasopressin, vasoactive intestinal polypeptide, and several other neuropeptides in the SCN was shown to be decreased after chronic alcohol (Madeira et al, 1997). Chronic alcohol also disrupts the responsiveness of the SCN to both photic and nonphotic phase resetting (Seggio et al, 2007). In addition, under constant conditions without the strong Zeitgeber of light, chronic alcohol shortens the periodicity of wheel-running behaviors (Seggio et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, chronic ethanol in hamsters apparently does not alter circadian clock re-entrainment (Mistlberger and Nadeau, 1992), while chronic ethanol can inhibit light-induced phase advances and (daytime) triazolam-induced phase advances in hamsters, but not light-induced phase delays (Seggio et al, 2007). Rosenwasser, et al (2005a,b) also showed that chronic ethanol affects circadian free-running periods in rats but not light-induced phase shifts.…”
Section: Discussion Ethanol Blocks Glutamate-induced Phase Shiftsmentioning
confidence: 99%
“…(Reid and Zee, 2004). Recent studies show that chronic ethanol alters the circadian free-running period in rats (Rosenwasser et al, 2005a,b) and inhibits light-and triazolam-induced phase shifts in hamsters (Seggio et al, 2007). However, little work has focused on whether acute ethanol affects circadian rhythms, and whether such effects involve direct actions on the master circadian clock located in the suprachiasmatic nucleus (SCN).…”
mentioning
confidence: 99%